(untitled) (Third Sector Social Economic Review, 2019)
Rapidly changing economic conditions and intense competitive environment in Kazakhstan requires businesses to carefully perform customer analyses for a more successful marketing. This study investigates the role of women in the purchase process of white goods in northern Kazakhstan (North, South, East and West). For this, we conscripted 396 Kazakh women living in Northern, Southern, Eastern and Western Kazakhstan and gave questionnaires to them. Collected data is interpreted with Confirmatory Factor Analysis (DFA) and Structural Equality Model (YEM).